Chaining and Prompting Technique of Behavior Modification to Improve Adaptive Skills in Child with Intellectual Disability - Marhani, Isnaeni; Mz, Ihsan; Syarif, Dina Fariza Tryani (International Journal of Universal Education, 2023)
Children with intellectual disabilities experience difficulties in understanding academics, adapting to their environment, and taking care of themselves. The ability to take care of oneself, which is also called adaptive life skills, is a top priority in an effort to teach children to achieve independence in taking care of themselves. It is hoped that children will be able to take care of themselves until they are completely independent without the help of others. One of the adaptive life skills that need to be trained in students with a diagnosis of intellectual disability is wearing all the clothes they need for school, starting from buttoning their clothes, fastening the buttons on their trousers and skirts, tying their shoelaces, and wearing socks. This research aims to evaluate the effectiveness of the chaining technique in improving the ability to wear socks in a student with mild intellectual disability. This research was conducted on KN, a 12-year-old student diagnosed with mild intellectual disability who was not yet fully able to put on socks which made her was still helped by her mother every day. This research design used a single-subject experimental design with 8 intervention sessions using chaining and prompting-type behavior modification techniques. Analysis was carried out by comparing the ability to put on socks before and after the intervention. The research results showed that the chaining and prompting techniques were successful in improving the adaptive life skills of putting on socks in a child diagnosed with mild intellectual disability.